Effect of Feeding Formaldehyde Treated Rapeseed Meal on Metabolic Profile of Surti Buffalo Heifers - Sorathiya, Kalpesh K.; Chaubey, Mahipal; Jadhav, Mahesh D.; Vahora, Safi G.; Patel, Vipul R.; Tabhani, Prakash M.; Lunagariya, Pravin M. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present experiment was conducted on Surti buffalo heifers to compare the graded level (0%, 0.25%, 0.50%, and 1% CP) of formaldehyde (HCHO)-treated rapeseed meal (RSM) in compounded concentrate mixture (CCM) on various metabolic indices. A total of twenty Surti buffalo heifers (16-18 months old; 164.68±5.43 kg) were divided into 4 homogeneous groups of 5 individuals each. The CCM was formulated using formaldehyde-treated rapeseed meal (@ 0%, 0.25%, 0.50%, or 1% HCHO-treated RSM CP), damaged wheat, corn grit, cottonseed extract, rice polish (fine), deoiled rice bran, rice flake bran, molasses, urea, calcite powder and common salt. FT-0 group was fed with CCM having untreated RSM, while FT-25, FT-50 and FT-100 groups were fed CCM having 0.25 %, 0.5 % and 1% CP from HCHO treated rapeseed meal. Results revealed non-significant differences in the serum total protein, albumin, globulin, cholesterol, albumin: globulin ratio and aspartate transaminase and alanine transaminase activities among different groups of heifers. However, serum urea concentration decreased (p
Keywords: Formaldehyde (HCHO); Metabolic profile; Rapeseed meal; Surti buffalo heifers